PENGARUH KONFLIK KEPENTINGAN TERHADAP KONSERVATISME AKUNTANSI DENGAN RISIKO LITIGASI DAN TIPE STRATEGI SEBAGAI VARIABEL PEMODERASI - Paramita, Febriana; Cahyati, Ari Dewi (JRAK (Jurnal Riset Akuntansi dan Komputerisasi Akuntansi), 2013)
Objective of this study is to examine influence conflict of interest to accounting conservatism and to test the effect of the type of strategy as moderating variables on the relationship between conflict ofinterest and accounting conservatism. The samples are 24 companies listed on the stock exchange.Using linear regression analysis and analysis of MRA results of the study showed that the conflict ofinterest has positive influence on accounting conservatism, conflict of interest a positive effect onaccounting conservatism with the risk of litigation as a moderating variable, Conflicts of interest are apositive influence on accounting conservatism with the type of strategy as a moderating variable.Conflicts of interest increase strong influence on the type of defender and weak on the type prospector